Smart home aquaponic system monitoring and control with internet of things using mobile application - Wan Hanisah, Wan Ibrahim; Nurul Amirah, Mohd Faizal; N. N., Mazlan; N. S., Hariyanto; Ruwaida, Abdul Rasid (Universiti Malaysia Pahang, 2023)
Food security has been a recurrent concern for numerous nations, including Malaysia. Climate change and population growth exacerbate this issue by increasing necessity food. In past few years, aquaponics has proven beneficial for fish and plant production, based on the idea that if every household can generate its own fish and plants, the nation's overall food consumption will reduce. The suggested smart house aquaponics system comprises an assortment of internet-connected sensors, actuators, and ESP32 microcontrollers that continuously monitor, adjust, and record the water and air quality of the fish tank. The Internet of Things (IoT) mobile application feature can alert the user in the event of an abnormal system state in terms of maintaining the health and growth of fish and plants. The Internet of Things (IoT) mobile application feature can alert the user in the event of an abnormal system state in terms of maintaining the health and growth of fish and plants. When the pH and turbidity thresholds are surpassed, the pumps are actuated to either fill or drain the tank. The results show that the design for a smart aquaponics system that can be used in a home is able to monitor and control all the parameters that are needed to cultivate wholesome fish and vegetation.